MANAJEMEN HUMAS DALAM MENINGKATKAN CITRA LEMBAGA (STUDI KASUS DI MADRASAH TSANAWIYAH AL AMIRIYAH BLOKAGUNG - Fauzan, Ahmad; Nadir, Mirhabun; Ikhwan, M. Bisri (STAI Ma'had Aly Al-Hikam Malang, 2024)
Public relations management is integral to the success of an institution in building and maintaining its public image. Especially in the context of education, public relations management plays an important role in attracting public interest, building trust, and managing positive perceptions of institutions. This study aims to analyze the public relations management practices carried out by Madrasah Tsanawiyah Al Amiriyah Blokagung and its impact on the image of the institution. This study used a qualitative approach with interview and observation data collection methods as well as docuentation. The result of this study is that effective public relations management in Madrasah Tsanawiyah Al Amiriyah Blokagung has helped improve the image of the institution. Through active communication, transparency, and the use of social media, this institution is able to build good relationships with its stakeholders and strengthen its position in the eyes of the public. This research provides insight into the importance of public relations management in the educational context and can be a reference for other educational institutions in improving their image through effective practices in public relations management.